The Instability of Dimeric Fc-Fusions Expressed in Plants Can Be Solved by Monomeric Fc Technology - Gattinger, Pia; Izadi, Shiva; Grünwald-Gruber, Clemens; Kallolimath, Somanath; Castilho, Alexandra (Frontiers in Plant Science, 2021)
The potential therapeutic value of many proteins is ultimately limited by rapid in vivo clearance. One strategy to limit clearance by metabolism and excretion, and improving stability of therapeutic proteins is their fusion to immunoglobulin fragment crystallizable region (Fc). The Fc region plays multiple roles in (i) dimerization for formation of” Y”-shaped structure of Ig, (ii) Fc-mediated effector functions, (iii) extension of serum half-life and (iv) a cost-effective purification tag. Plants and in particular Nicotiana benthamiana have proven to be suitable expression platforms for recombinant therapeutic proteins including monoclonal antibodies. Despite the enormous success one limitation comes with the expression of Fc-fused therapeutic proteins in plants. Many Fc-fusion proteins expressed show different degrees of instability resulting in high amounts of Fc-derived degradation products. To address this issue, we used Erythropoietin (EPO) as a reporter protein and evaluated the efforts to enhance expression of full-length EPO-Fc fusions targeted to the apoplast of N. benthamiana. Our results show that instability of the fusion protein is independent from the Fc origin or IgG subclass and from the peptide sequence used to link the two domains. We also show that similar instability occurs upon expression of individual heavy chains of monoclonal antibodies and ScFv-Fc that mimic the “Y”-shape of full-size antibodies but lack the light chain. We propose that in this configuration, steric hindrance between the protein domains leads to physical instability. Furthermore, we show that contrasting to IgG-Fc domains, alternative fusion partners, not able to dimerize, allow the expression of monomeric fusion proteins that are fully stable. Finally, we discuss the limitations of Fc-fusion technology in N. benthamiana transient expression systems and suggest strategies to optimize the Fc-based scaffolds on their folding and aggregation resistance in order to improve stability.